Analisis Pesan Moral dalam Puisi “Senja di Pelabuhan Kecil” Karya Chairil Anwar - Ina Sumiati; Sefina Aprilia Soleha (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
A literary work is a written or oral work that is conveyed using language as the main medium, which is a person's expression created based on thoughts, experiences, opinions and feelings. Poetry is a form of literary art that combines the beauty of language, emotion and imagination to express feelings and ideas in depth. Poetry contains the author's emotions and experiences that remain imprinted in memory. Poetry has hidden meanings wrapped in rhyming language so it is more interesting to read. The author is interested in analyzing the poem "Senja di Pelabuhan Kecil" by Chairil Anwar, because the poem is formed with a straightforward language but has a broad meaning and contains many moral messages in the poem. The aim of this research is to find out the moral message in Chairil Anwar's poetry and to improve the author's understanding of the pragmatic approach. This research method uses a qualitative descriptive method that analyzes and explains the moral message of the poem "Senja di Pelabuhan Kecil" by Chairil Anwar using observation studies. The pragmatic approach is an approach to literary criticism that wants to show readers' impressions and acceptance of literary works. Based on the results of the analysis of the poem "Sunja di Pelabuhan Kecil" it can be concluded that this poem contains a moral message about sincerity in accepting a loss and not dwelling on sadness.